Social Gradients in the Health of Indigenous Australians - Shepherd, Carrington; Li, Jianghong; Zubrick, Stephen (American Public Health Association, 2012)
The pattern of association between socioeconomic factors and health outcomes has primarily depicted better health for those who are higher in the social hierarchy. Although this is a ubiquitous finding in the health literature, little is known about the interplay between these factors among indigenous populations. We begin to bridge this knowledge gap by assessing evidence on social gradients in indigenous health in Australia. We reveal a less universal and less consistent socioeconomic status patterning in health among Indigenous Australians, and discuss the plausibility of unique historical circumstances and social and cultural characteristics in explaining these patterns. A more robust evidence base in this field is fundamental to processes that aim to reduce the pervasive disparities between indigenous and non-indigenous population health.